BUILDING THE CLIMATE MOVEMENT (Utah Environmental Law Review; Vol 29 No 1 (2009))
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} We have heard an awful lot about climate change in the last day and a half and I am only going to provide the littlest bit of a summary here to kind of try to bring us to where I think we are now. I am going to do it just by recounting my experiences since I am one of the relative few who have gotten to watch the whole history of this thing despite that it was really only twenty years ago that climate change broke out into the national conversation. I am just going to provide a quick history to take us to where I think we need to be now.